The Influence Of Fairness Of Price And Tourist Facilities On Tourist Loyalty Through Lake Toba Tourist Trust And Satisfaction - Halimatu Saddiah Marpaung; Syaifuddin Syaifuddin; Nagian Toni (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study uses a quantitative type approach to examine certain populations or samples. Data collection uses research instruments and data analysis is statistical in nature, with the aim of testing the hypotheses that have been set. In this study the population is tourists who have visited Lake Toba at least once. as. The samples in this study consisted of 140 samples. The results of the study show that the fairness of prices has a large influence on the trust and satisfaction of Lake Toba tourists. because at a reasonable price, visitors will feel they don't need a lot of money to visit Lake Toba. In addition, tourist facilities also have an influence on tourist satisfaction. That's because with the availability of facilities on Lake Toba, tourists will feel happy and comfortable. With the availability of facilities, tourists will feel that visiting Lake Toba will be more interesting and enjoyable. so it is concluded that the fairness of prices and tourist facilities greatly have an influence on the trust and satisfaction of Lake Toba tourists.